Republica Moldova între opțiunea europeană şi cea euroasiatică - Mocanu, Victor; Dumbrăveanu, Andrei (Calitatea Vieții, 2014)
Since its independence, the state of Moldavia has been oriented towards the family of European Union. But the European direction can be replaced by the pro-Eurasian direction, promoted by pro-Russian political forces in this country. In this respect, people options are divided. The sociological study entitled: “Vox Populi – The Republic of Moldova” during October 21–November 2, 2013 period, initiated and developed by the Association of Sociologists and Demographs from the Republic of Moldavia has researched both European and Eurasian options. The research sample included 1 192 respondents from 79 localities, without the Transnistria region, and it was representative for the adult population, with a maximum error of ± 2.8%. The authors of the study present the reasons of these options, quantitatively and qualitatively. Their conclusions are the following: the Moldavian population knows very little the risks and the benefits of the accession to the European Union. Its sources of information are the mass-media, first, the tv, but there are no special editions devoted to this association. From case to case, other sources are: the internet, the discussions with friends, close people. The population does not know about the infrastructure development projects, of training, of joint ventures with EU Member States, or about the grants which started in 2010, since the “Alliance for European Integration” coalition is in state. Group interests of the politicians, the judicial corruption and its involvement in press scandals have led to the collapse of power and have eclipsed the European path declared by the Governors. In these circumstances, taking advantage of the precarious social-economic situation, the Communist opposition, hostile to the idea of associating with the European Union, with the support of the Russian Federation, initiated terrorist actions, disinformation, mass manipulation of the population, for the accession of the Republic of Moldavia to the Customs Union Russia–Belarus–Kazakhstan, practically, for the reconstruction of the neo-liberal principles of Imperialist Russia. During the next EU Summit from Vilnius, the Government of the country will join all the efforts of civil society, NGOs in the Republic of Moldavia, to demonstrate that they have the ability to organize, convince and attract people in knowing the advantages and disadvantages of an association to the European Union. All this, in order to avoid the manipulation of the population and its disinformation, its use against the national interest by hostile political forces.